A hybrid extreme machine learning model for predicting heart disease - M. Ahmed, Abdelmoty; Bataineh, Bilal; Shakah, Ghazi; O. Al Enany, Marwa; M. Aboghazalah, Maie; M. Khattab, Mahmoud (Institute of Advanced Engineering and Science, 2025)
Heart disease (HD), the leading cause of death for adults over 65, can affect anyone at any time. Additionally, modern lifestyles, poor diets, and other factors have led to an increased risk of HD among teenagers. One significant challenge is managing and analysing vast amounts of data, often surpassing terabytes, which is crucial for researching, diagnosing, and predicting cardiovascular diseases quickly. To enhance primary health care, especially in early and rapid diagnosis of heart attacks and to assist less experienced doctors in understanding clinical HD data, we propose a hybrid method called the